Post-partum reproductive behavior regarding contraception and breastfeeding in rural Bangladesh - Gazi, Rukhsana; Karim, Fazlul; Chowdhury, AMR; Mahmud, Shah Noor (BRAC Research and Evaluation Division (RED), 2019)
The study was aimed to obtain information on knowledge of mothers about fecundity after childbirth and to explore the reproductive behavior of the mothers related to breastfeeding, postpartum abstinence and contraceptive practices. This was a comparative study between the WHOP of BRAC {Bogra Sadar thana) and a non program {Joypurhat) area. Data was collected by five female interviewers retrospectively from a total of 400 randomly selected women who were in 6 to 12 week of their post partum period. Women are most unlikely to adopt contraception unless they resume ft1enstruation as they believe that fecundity returns only after the resumption of menstruation. Whereas they tend to resume sexual activity within 40 days after childbirth. A significant higher proportion of women in the program area were found to have fed colostrum than in the non program area (92% vs 71 %), they were unlikely to be breast feeding exclusively. Mothers are loosing the contraceptive benefits of breastfeeding very soon after delivery and are at risk of subsequent conception. As reliance on lactational infertility alone is not advisable due to the early weaning and partial breast feeding, the program should increasingly promote the use of appropriate contraceptive methods from the early postpartum period.